FOREIGN EXPERIENCE OF PROVIDING STATE SOCIAL DEVELOPMENT AND REGIONAL SECURITY - Pomaza-Ponomarenko A. L. (Pressing Problems of Public Administration, 2016)
The analysis of speci city of state to ensure social development and regional security in Europeancountries has been done. The basic directions of the further social development in Ukraine in the contextof its security have been designated.